EFISIENSI PENGGUNAAN FAKTOR PRODUKSI PADA USAHA TERNAK BABI SKALA RUMAH TANGGA DI KECAMATAN ENDE TIMUR KABUPATEN ENDE (Efficiency of using production factors on pig household scale business in Ende Timur District, Ende Regency) - Agnetia Siesta Sani; Solvi M Makandolu; Johanes G. Sogen (JURNAL NUKLEUS PETERNAKAN, 2020)
Pig farmers in rural areas generally use agricultural by product from crops and horticulture as animal feed. A survey focused on pig household scale business was carried out with the aims were to: 1) analize the income of pig household scale farmers; 2) analize the factors that influence the cash income of pig household scale farmers; and 3) analize the efficiency of using production factors in pig household scale business. Sampling is done in two stages manner. The first, to determine three sample villages purposively. The second, determining 20 pig farmers in each selected village by applying non-proportional random sampling in order to obtain 60 representative respondents. Data were analyzed using a descriptive method approach and continued with income analysis, correlation-regression analysis and analysis of efficiency. The results showed that the total income obtained was IDR 30,924,132/year where 59.74% was cash income. The results of statistical analysis show that the factors that influence the cash income of farmers are the number of pigs raised and the cost of feed (P <0.05) while the capital and cost of pens and equipment have no significant effect on household cash income (P> 0.05). The results of efficiency analysis indicate that technically, the use of production factors in pig household scale business in East Ende District is efficient but economically has not been achieved. Therefore it is necessary to reorganize the business through efforts of increasing the number of pigs raised, ceteris paribus other factors.